2023
DOI: 10.1007/s11547-023-01668-9
|View full text |Cite
|
Sign up to set email alerts
|

Pivotal role of multiphase computed tomography angiography for collateral assessment in patients with acute ischemic stroke

Abstract: The cerebral collateral circulation is the main compensatory mechanism that maintains the ischemic penumbra viable, the tissue at risk for infarction that can be saved if blood flow is restored by reperfusion therapies. In clinical practice, the extent of collateral vessels recruited after vessel occlusion can be easily assessed with computed tomography angiography (CTA) using two different techniques: single-phase CTA (sCTA) and multi-phase CTA (mCTA). Both these methodologies have demonstrated a high prognos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 103 publications
0
1
0
Order By: Relevance
“…While it is recognized that perfusion techniques such as computed tomography perfusion (CTP) can provide information on collateral circulation, they fall short in direct visualization. In contrast, CTA techniques, including single-phase CTA (sCTA) and multiphase CTA (mCTA), excel in the identification of occluded points and the visualization of collateral filling ( 33 ). mCTA includes three acquisition stages with a commendable temporal resolution, allowing a more detailed and reliable assessment of collateral vessels.…”
Section: Clinical Studymentioning
confidence: 99%
“…While it is recognized that perfusion techniques such as computed tomography perfusion (CTP) can provide information on collateral circulation, they fall short in direct visualization. In contrast, CTA techniques, including single-phase CTA (sCTA) and multiphase CTA (mCTA), excel in the identification of occluded points and the visualization of collateral filling ( 33 ). mCTA includes three acquisition stages with a commendable temporal resolution, allowing a more detailed and reliable assessment of collateral vessels.…”
Section: Clinical Studymentioning
confidence: 99%
“…Another important observation was that the tissue under severe hypoperfusion survives a shorter period of time and that the tissue in "penumbra" will inevitably progress to irreversible damage, which is to say, the "core" grows over time if perfusion is not restored [25]. What determines the survival of the penumbra is indeed the collateral circulation, but it cannot save the penumbra indefinitely [40].…”
Section: Collateral Circulation and Neuromodulationmentioning
confidence: 99%
“…NCCT recognizes early ischemic changes (areas of weak parenchymal hypoattenuation such as focal hypodensity, obscuration of lentiform nucleus, loss of gray-white matter differentiation, loss of insular ribbon) corresponding to the infarct core and estimates their extent using the semiquantitative Alberta Stroke Program Early CT Score (ASPECTS) methodology but does not detect the ischemic penumbra [10] . CTA identifies the occlusion site and provides a detailed evaluation of collateral supply using two different techniques, single-phase CTA (sCTA) and multi-phase CTA (mCTA) but does not provide information about infarct core and ischemic penumbra [11] . Conversely, a recent randomized controlled trials (RCTs) showed benefit from reperfusion therapies in the late time window using advanced imaging [9] .…”
Section: Introductionmentioning
confidence: 99%